Mild N‐Alkylation of Amines with Alcohols Catalyzed by the Acetate Ru(OAc)2(CO)(DiPPF) Complex. Issue 58 (19th September 2017) - Figliolia, Rosario; Baldino, Salvatore; Nedden, Hans G.; Zanotti‐Gerosa, Antonio; Baratta, Walter
Abstract: The acetate complex Ru(OAc)2 (D i PPF) (2 ) obtained from Ru(OAc)2 (PPh3 )2  (1 ) and 1, 1′‐bis(diisopropylphosphino)ferrocene (D i PPF) reacts cleanly with formaldehyde affording Ru(OAc)2 (CO)(D i PPF) (3 ) in high yield. The monocarbonyl complex 3 (0.4‐2 mol %) efficiently catalyzes the N‐alkylation of primary and secondary alkyl and aromatic amines using primary alcohols ROH (R=Et, n Pr, n Bu, PhCH2 ) under mild reaction conditions (30–100 °C) with an alcohol/amine molar ratio of 10‐100. Formation of the monohydride RuH(OAc)(CO)(D i PPF) (4 ) has been observed by reaction of3 with i PrOH in the presence of NEt3 at RT through an equilibrium reaction. Abstract : Amico rutenio : The complex Ru(OAc)2 (CO)(D i PPF), easily prepared by carbonylation of Ru(OAc)2 (D i PPF) with H2 CO, efficiently catalyzes the alkylation of primary and secondary amines with alcohols under mild reaction conditions. Addition of a suitable amount of trifluoroacetic acid increases the rate of reaction. Evidence of the formation of the monohydride RuH(OAc)(CO)(D i PPF) species is provided.